2020
DOI: 10.3390/ijms21072486
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of Duplex and Triplex Laminated Edible Films Using Whey Protein Isolate, Gelatin and Sodium Alginate

Abstract: The objective of this study was to assess the ability of producing laminated edible films manufactured using the following proteins; gelatin (G), whey protein isolate (WPI) and polysaccharide sodium alginate (SA), and to evaluate their physical properties. Additionally, films’ preparation employing these ingredients was optimized through the addition of corn oil (O). Overall, 8-types of laminated films (G-SA, G-WPI, SA-WPI, SA-G-WPI, GO-SAO, GO-WPIO, SAO-WPIO and SAO-GO-WPIO) were developed in this study. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, the evaluation of whey, as well as investment in research and technology, are fundamental advances for the expansion of activities in the dairy industry worldwide 73 . In this context, the manufacture of films with edible characteristics is of great interest to the food and packaging industries today, due to the emerging environmental demands regarding the use of plastics and the need for alternative biodegradable materials that can provide storage and maintenance functions for a shelf life similar to conventional synthetic packaging forms 74 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the evaluation of whey, as well as investment in research and technology, are fundamental advances for the expansion of activities in the dairy industry worldwide 73 . In this context, the manufacture of films with edible characteristics is of great interest to the food and packaging industries today, due to the emerging environmental demands regarding the use of plastics and the need for alternative biodegradable materials that can provide storage and maintenance functions for a shelf life similar to conventional synthetic packaging forms 74 …”
Section: Resultsmentioning
confidence: 99%
“…73 In this context, the manufacture of films with edible characteristics is of great interest to the food and packaging industries today, due to the emerging environmental demands regarding the use of plastics and the need for alternative biodegradable materials that can provide storage and maintenance functions for a shelf life similar to conventional synthetic packaging forms. 74 As discussed throughout this review, several studies have reported promising results regarding the use of whey as an ingredient in the manufacture of edible films and taking into account the Goals for Sustainable Development (SDGs) recommended by the United Nations (UN). Figure 5 shows the main positive impacts generated by the use of whey for the production of edible and biodegradable polymeric films.…”
Section: Considerations Of Environmental and Social Aspectsmentioning
confidence: 99%
“…11,13,14 A plasticizer is often added to the film-forming solution to improve the flexibility of the SA film. Glycerol has been extensively used as a plasticizer for SA films 3,11,14 due to its low cost and absence of safety concerns, in addition to its effectiveness in providing flexible films. 16,17 Several previous studies have reported that SA films showed good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin- and whey protein-based materials have been rarely approached in research regarding the production of packaging materials; however, obtaining and the characterization of edible films have been described in the literature [ 29 , 49 , 50 ]. A composite with antibacterial properties based on whey protein that combined gelatin, nanoclay, orange-peel extract, and tripolyphosphate was studied by Shams [ 51 ].…”
Section: Introductionmentioning
confidence: 99%